IDENTIFICATION OF SECONDARY METABOLITES CHLOROFORM EXTRACT KARAMUNTING STEMS (RHODOMYRTUS TOMENTOSA) - Yenihayati (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2018)
ABSTRACT Karamunting plants are plants that can be used for medicine and all parts of the karamunting plant can be used such as leaves, stems and roots. This plant is widely found in Kal-teng. Karamunting plants are found on mountain slopes, shrubs and fields that are not too arid. Karamunting is believed to cure diabetes millitus (DM), menstruation, blood loss, inflammation of blood vessel walls, clotting (thromboangitis) and anti-malaria. The purpose of this study was to determine the class of secondary metabolites found in Karamunting stems (Rhodomyrtus Tomentosa). This research process begins by making karamunting growth powder. The powder is 100 gram extracted with chloroform. The extract obtained was tehn dissolved in chloroform and distilled water in a ratio of 1 : 1. Then the obtained solution was shaken well and left for 15 minutes, so that two layers of chloroform and water were formed. The chloroform layer at the bottom is used to identify steroid compounds, terpenoids and alkaloids. While the water layer is used to identify flavonoids, phenolics and saponins. The results of identification with color tests showed that karamunting plants contain saponin, terpenoids and flavonoid secondary metabolites.